Dinamika Perkembangan Industri Tenun H. Ridwan By di Nagari Kubang, Kecamatan Guguak, Kabupaten Lima Puluh Kota (1961-2019) - Fitriani, Desi; Midawati, Midawati; Rahmi, Yulia (Analisis Sejarah, 2024)
This article examines the development of the H. Ridwan By weaving industry in Nagari Kubang from 1961 to 2019, spanning three leadership periods: Ridwan, Risna, and Yulia Rahmi. Employing a historical research method, involving heuristic data collection (archival documents, interviews), source criticism, interpretation, and historiography, the study reveals the evolution of the industry from its inception as a family-owned business in 1961. The research highlights significant advancements across leadership transitions, encompassing new motifs, product diversification, workforce expansion, and marketing strategies. These developments have positively impacted the sustainability of the H. Ridwan By weaving enterprise, ensuring its continued existence until 2019.